C9/12 Ribbon‐Like Structures in Hybrid Peptides Alternating α‐ and Thiazole‐Based γ‐Amino Acids. Issue 69 (15th November 2017) - Bonnel, Clément; Legrand, Baptiste; Simon, Matthieu; Martinez, Jean; Bantignies, Jean‐Louis; Kang, Young Kee; Wenger, Emmanuel; Hoh, Francois; Masurier, Nicolas; Maillard, Ludovic T.
Abstract: According to their restricted conformational freedom, heterocyclic γ‐amino acids are usually considered to be related to Z ‐vinylogous γ‐amino acids. In this context, oligomers alternating α‐amino acids and thiazole‐based γ‐amino acids (ATCs) were expected to fold into a canonical 12‐helical shape as described for α/γ‐hybrid peptides composed of cis‐ α/β‐unsaturated γ‐amino acids. However, through a combination of X‐ray crystallography, NMR spectroscopy, FTIR experiments, and DFT calculations, it was determined that the folding behavior of ATC‐containing hybrid peptides is much more complex. The homochiral α/( S )‐ATC sequences were unable to adopt a stable conformation, whereas the heterochiral α/( R )‐ATC peptides displayed novel ribbon structures stabilized by unusual C 9/12 ‐bifurcated hydrogen bonds. These ribbon structures could be considered as a succession of pre‐organized γ/α dipeptides and may provide the basis for designing original α‐helix mimics. Abstract : A ribbon structure, stabilized by C9/12 ‐hydrogen bonds, was determined in heterochiral hybrid peptides alternating α‐ and thiazole‐based γ‐amino acids (see figure).